Aboriginal employment opportunities in a low-carbon economy. (30th October 2019) - Marinova, Dora; Webster, Philip; Rooney, Angela; McRae, Anthony; Seemann, Kurt; Garlett, Ashley; Fiocco, Paul
This study explores opportunities for Australian Aboriginal youth to participate in a low-carbon economy and avoid further marginalisation. The concepts of low-carbon economy, green jobs and employment for transitioning to sustainability are discussed, followed by the case of a training organisation looking after Aboriginal youth. Outcomes from a survey of 155 graduating students and deliberative workshops with 60 participants conducted in Perth, Western Australia in 2016 are presented. The analysis shows: 1) Aboriginal youth are not clear about the meaning of green jobs but want to learn about them; 2) the low-carbon economy plays a double role in skills development requiring new capacity for opportunities, such as in renewable energy, and strengthening the importance of traditional knowledge and familiarity with the Australian continent, represented through ranger programs, use of native plants and rehabilitation of deteriorated land areas. Barriers to Aboriginal employment in green jobs and ways to overcome them are also discussed.